Impact of scholarships on university academic performance: a comparative analysis of students with and without scholarships - Berlanga, Vanesa; Corti, Franciele (Frontiers in Education, 2025)
Within the framework of the European Higher Education Area (EHEA), university scholarships have become a key tool to guarantee equity and inclusion in higher education. These policies seek to reduce the socioeconomic barriers faced by students and to promote their access, permanence, and academic success. This study focuses on analyzing the impact of scholarships on the academic performance, continuity, and graduation of students at the Universitat Abat Oliba CEU in Spain during the period 2020–2024. Based on a descriptive-comparative design and using an institutional database with information on 6,295 students, the differences between the groups with and without scholarships are examined. The variables analyzed include demographic, academic and performance data, such as cumulative grade point average, credits enrolled, presented, and passed, and success and achievement rates. The analysis was performed using advanced statistical tools to identify relevant patterns and trends. The results show that students with scholarships not only access university more frequently, but also perform better on key indicators, such as success rate and achievement rate, compared to students without scholarships. These findings reinforce the role of scholarships as a determinant of academic success, although they also reveal inequalities in the performance of non- scholarship students, suggesting the need for additional interventions. This study provides relevant empirical evidence for the design and evaluation of educational policies that seek to promote more inclusive higher education and equity. It also highlights the importance of implementing complementary support strategies to ensure the academic success of all students, regardless of their socioeconomic status.